INVESTIGATING THE INFLUENCE OF DIGITAL PAYMENTS ON THE EVOLUTION OF BANKING SYSTEMS AND CONSUMER HABITS - Aripin, Zaenal; Anggraeni, Vilma Dewi; Yulianty, Farida (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2024)
Background:Digital payment systems revolutionized financial transactions through mobile wallets, contactless payments, and cryptocurrency, challenging traditional banking models. Aims:This study investigates digital payment adoption's influence on banking system evolution and consumer financial habits. Research Method:Employing longitudinal mixed-methods, we analyzed data from 15 banks across six countries (2019-2024), incorporating transaction pattern analysis and insights from 2,500 consumer surveys. Results and Conclusion:76% of consumers regularly use digital payments; cash transactions declined 45%. Transaction frequencies increased 62% with enhanced budgeting awareness. Banks reduced branches 18% while enhancing cybersecurity investments. Contribution:The study contributes to understanding co-evolution of payment technologies and banking systems, providing strategic insights for managing digital transformation in financial services. This study investigates the influence of digital payments on the evolution of banking systems and consumer financial habits, examining adoption patterns, behavioral shifts, and systemic implications. Research Method: Employing a longitudinal mixed-methods approach, this research analyzes transaction data from 15 banks across six countries over a five-year period (2019-2024), complemented by surveys of 2,500 consumers and interviews with banking executives and fintech leaders.   Results and Conclusion: Findings reveal that digital payment adoption has grown exponentially, with 76% of consumers now using at least one digital payment method regularly. This shift has driven significant changes in consumer behavior: reduced cash usage (declining 45% on average), increased transaction frequency (up 62%), and greater financial tracking and budgeting awareness. Banks have responded by restructuring operations, reducing physical branches by 18%, and investing heavily in digital infrastructure. Contribution: This research contributes to understanding the co-evolution of payment technologies and banking systems, providing insights into consumer adaptation patterns and strategic imperatives for financial institutions navigating digital transformation.